2008
DOI: 10.1002/polb.21585
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and mechanical properties of a novel amorphous polyamide/nanoclay nanocomposite

Abstract: A novel amorphous polyamide/montmorillonite nanocomposite based on poly(hexamethylene isophthalamide) was successfully prepared by melt intercalation. Wide angle X-ray diffraction and transmission electron microscopy showed that organoclay containing quaternary amine surfactants with phenyl and hydroxyl groups was delaminated in the polymer matrix resulting in well-exfoliated morphologies even at high montmorillonite content. Differential scanning calorimetry results indicated that clay platelets did not induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 57 publications
8
41
1
Order By: Relevance
“…As can be seen, the Young's modulus increased substantially with the addition of OMMT. The increase in modulus (28%) was similar to that obtained in other aPA based PNs [25][26][27] with the same clay content. The increases in both the modulus and the yield stress were for the most part independent of the mSEBS content, and therefore, their relative importance increased at increasing rubber contents.…”
Section: Mechanical Propertiessupporting
confidence: 83%
“…As can be seen, the Young's modulus increased substantially with the addition of OMMT. The increase in modulus (28%) was similar to that obtained in other aPA based PNs [25][26][27] with the same clay content. The increases in both the modulus and the yield stress were for the most part independent of the mSEBS content, and therefore, their relative importance increased at increasing rubber contents.…”
Section: Mechanical Propertiessupporting
confidence: 83%
“…The increase in elongation at break also shows that kaolin can also improve the impact toughness of the blend. This is consistent with the observations reported earlier [33].…”
Section: Resultssupporting
confidence: 94%
“…These two peaks in N(6), as reported by Sun et al,5 referred to the α‐form crystals, which were thermodynamically stable and represented by the mean peak at nearly 220°C, and the other peak, which was as a shoulder of the mean peak, was due to the γ form at nearly 212–215°C. The two peaks in N(6,6) at 260 and 252°C were related to the α and β forms, respectively, as reported by Zhang3 and Xin et al27 These two peaks' behavior in N(6,6) indicated that the clay could induce and enhance the β‐form crystals, which appeared as a shoulder for the mean α peak, whereas for the 70 wt % N(6)/30 wt % N(6,6) blend, the melting temperature for the stable crystal structure was 210°C, and the melting temperature for the other crystal form was nearly 205°C. An acceptable theory for the two peaks' behavior was put forward by Roberts28, 29 and Holdsworth and Jones,30 who said that the first peak, which appears as a shoulder for the mean peak, results from the melting of imperfect crystals and that the mean peak results from the melting of more perfect crystals, which results from the recrystallization of imperfect crystals heating.…”
Section: Resultssupporting
confidence: 75%
“…Many researchers have studied the effects of nanoclay on polymers on the basis of single polymer matrixes, including nylon 6,6 [N(6,6)],1, 2 nylon 6 [N(6)],3–5 polypropylene (PP),6, 7 polystyrene,8, 9 and others.…”
Section: Introductionmentioning
confidence: 99%